2012
DOI: 10.35536/ljb.2012.v1.i1.a4
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Women’s Turnover Intentions in Pakistan’s Public Universities

Abstract: The aim of this study is to test the impact of women's job satisfaction on their turnover intentions, specifically for those employed in the education sector. Using a sample drawn from two different universities in Lahore, Pakistan, we measure their levels of job satisfaction by evaluating their general working conditions, pay and potential for promotion, professional relationships, use of skills and abilities, and activities assigned. We find that flexible working hours, workplace location, performance apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…It is basically the response of an employee towards his/her work experience. (Gruneberg, 1979) said that it is an emotional response towards their job, as to how they feel about their job and work conditions (Bushra, 2012). It is one of the important factors leading to success in the organization.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…It is basically the response of an employee towards his/her work experience. (Gruneberg, 1979) said that it is an emotional response towards their job, as to how they feel about their job and work conditions (Bushra, 2012). It is one of the important factors leading to success in the organization.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Aliya Bushra (2012) in her work on job satisfaction and Women's' turn over intentions in Pakistan public universities and the results found that adaptable working hours, working environment area, execution evaluation and ability use take an extremely positive result on turn over goals, while proficient self-sufficiency, professional stability and advancement take an inverse impact on employment fulfillment and turn over expectations. Hind A. M. Bader ,IntanH.M.Hashim and Norzarina Mohd Zaharim ( 2013) worked on job satisfaction among bank employees in eastern Libya and the findings of the current study publicized that bank employees in eastern Libya stated a great level of job satisfaction in all aspects of their job, but the factors of gender, age and type of occupation occur no substantial influence on the level of job satisfaction, marital status, educational level, city and the education of work occur substantial impact on the level of job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Employees exhibit negative attitudes like intent to leave and no commitment towards the organization when they perceive that their organization is not treated them fairly (DeConinck & Johnson, 2009). Turnover intentions of few employees create problems for the entire organization, it is a form of expense for organization because when employees will leave, organizations would require new employees and for that organization has to bear extra cost of recruitment, selection, training etc (Bushra, 2012). In the previous studies, it's been noted that workplace bullying is a very important forecaster and predictor of turnover intention, when there is workplace bullying turnover rate would increase (Van Schalkwyk, Els, & Rothmann Jr, 2011).…”
Section: Workplace Bullying and Turnover Intentionsmentioning
confidence: 99%